2020
DOI: 10.1063/5.0006496
|View full text |Cite
|
Sign up to set email alerts
|

Al diffusion at AlN/Si interface and its suppression through substrate nitridation

Abstract: One of the challenges for GaN-on-Si radio frequency (RF) device applications is the RF loss, which is mainly associated with a parasitic channel formed at the interface of AlN and high-resistivity Si substrates. However, the type of conductivity and formation mechanism of the parasitic channel remains controversial. Here, we report unambiguous evidence of Al diffusion at the AlN/Si interface and its effect on RF loss. Hall measurements reveal p-type conductivity at the interface. By combining with secondary io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…After Si oxide removal under H 2 around 1000 °C, a thin 20 nm nucleation layer is grown at low temperature (1100 °C thermocouple setpoint, real temperature around 900 °C). The nucleation is performed using a NH 3 preflow to limit the risk of Al diffusion towards the substrate 13 . Then, the substrate temperature is rapidly increased to grow the AlN film with a total thickness up to 200 nm.…”
Section: Resultsmentioning
confidence: 99%
“…After Si oxide removal under H 2 around 1000 °C, a thin 20 nm nucleation layer is grown at low temperature (1100 °C thermocouple setpoint, real temperature around 900 °C). The nucleation is performed using a NH 3 preflow to limit the risk of Al diffusion towards the substrate 13 . Then, the substrate temperature is rapidly increased to grow the AlN film with a total thickness up to 200 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Structure Loss Time Meneghesso G. [29] Si/(AlGa)N/GaN/AlN 0.9 dB/mm @ 10 GHz 2013 Cao L. [30] Si/(AlGa)N/GaN/AlGaN 0.58 dB/mm @ 5 GHz 2017 Cordier Y. [15] Si/(AlGa)N/GaN 0.3 dB/mm @ 10 GHz 2018 Cao L. [20] Si(HR)/(AlGa)N/GaN/AlGaN 0.27 dB/mm @ 20 GHz 2018 Chandrasekar H. [28] GaN-on-Si 0.6 dB/mm @ 6 GHz 2019 Wei L. [11] Si/AlN 1.47 dB/mm @ 6 GHz 2020 Ghosh S. [31] Si/AlN 12.7 dB/mm @ 5 GHz 2021 Si/(AlGa)N/GaN/AlN 0.9 dB/mm @ 10 GHz 2013 Cao L. [30] Si/(AlGa)N/GaN/AlGaN 0.58 dB/mm @ 5 GHz 2017 Cordier Y. [15] Si/(AlGa)N/GaN 0.3 dB/mm @ 10 GHz 2018 Cao L. [20] Si(HR)/(AlGa)N/GaN/AlGaN 0.27 dB/mm @ 20 GHz 2018 Chandrasekar H. [28] GaN-on-Si 0.6 dB/mm @ 6 GHz 2019 Wei L. [11] Si/AlN 1.47 dB/mm @ 6 GHz 2020 Ghosh S. [31] Si/AlN…”
Section: Authormentioning
confidence: 99%
“…For the GaN HEMT RF device, there is still a very serious challenge, which is that the conductive layer is more likely formed at the interface between the Si substrate and the nucleation layer. The GaN HEMT device usually introduces an AlN nucleation layer between the Si substrate and the GaN layer, but its Al atoms will diffuse on the surface and on the inside of the Si substrates to form a conductive layer, which will cause RF loss in the devices working at high frequency and results in limiting output power and efficiency [11]. According to reports, wafer warpage caused by mismatch is greatly improved by adding a suitable Al(Ga)N stress control layer [12], and gold-free ohmic contacts technology has achieved a breakthrough in the compatibility issue mentioned above [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The physical origin of this parasitic conduction is still under debate [23]. For instance, several authors have reported Ga/Al diffusion into the silicon substrate in the order of 10 16 cm -3 to 10 18 cm -3 with up to 3 m roll-off into the silicon substrate [24]. The Ga/Al atoms into the Si substrate act as acceptors and form a p-type conductive layer at the top surface of the substrate.…”
Section: Physical Originmentioning
confidence: 99%